Solution synthesis of monodispersed nanocrystalline FCC-, e- and HCP-Cobalt particles - Perales, Oscar (2003)
The systematic research of the "polyol process" applied to the production of metallic Cobalt particles is presented. In this approach, the control of the reaction kinetics and the metal particla size were achieved through a suitable selection of the solution chemistery in the ethylene glycol (EG)- or Trimethylene glycol (TMEG)-Cobalt (II) system. The adition of hydroxil ions into the Co solution in EG caused a dramatic shorteninig of the reaction time. This sortening in reaction time permited a convenient control of the size of sub-micron Co particles in reaction time with a highmonodispersity. A further tailoring of the particle size was achieved by using acetate iones. Under the latter condition, monodispersed Co particles of about 220-nm in diameter were produced. The Co particles were polycristalline and their structure consisted of either fcc or fcc/hcp mixtures. The saturation magnetization (Ms) and coercivity (Hc) at room temperature ranged from 65 to 162 emu/g and 35 to 199 Oe, respectively. In presence of Pt ions, Cobalt nanoparticles as small as 25 nm were synthesized. Depending on syntehsis conditions, metastable e-Co and/or hcp-Co were stabilized at the nanosize livel. The high coercivity-hcp phase was produced without need of the annealing. The Ms and HC of the Co particles synthetized in presence of Pt ions, varied from 53 to 77 emu/g and 222 to 535 Oe, respectively.